Antenna obstruction cloaking - Lundqvist, Dennis; Wilhelmsson, Agnes (My University, 2024)
This report theoretically investigates different techniques of electromagnetic cloaking and anti-scattering on a cylindrical metallic object, e.g. a cord or a pole, along the vertical axis obstructing a vertically polarized antenna (i.e. a worst case scenario in terms of scattering) at 9.5 GHz/X-band. Multiple ’shells’ around the pole obstructions have been designed with different materials and shapes, for simulations around metallic poles of diameters 5 cm and 10 cm at different distances from the antenna. A total of 4 designed shells have been simulated in Ansys 3D High Frequency Simulation Software (Ansys HFSS) in order to evaluate their performance in terms of realized gain and average sidelobe level in the antenna’s forward direction fordifferent steering angles in the H-plane/azimuth plane. The evaluated shells around the poles were 1) a layer of thin radiation absorbent material made out of ferrites (narrowband absorbent), 2) a rhomb made out of PEC, 3) a rhomb made out thick radiation absorbent material with increasing conductivity (wideband absorbent) and 4) a rhomb made out of PEC (e.g. shell 2) supplemented with a dielectric outer edge and PEC strips around the circumference of the structure. Additionally, the project evaluated the requirements of meta-material cloaks and how to design them in practice. Although meta-materials have been a hot topic the recent years for electromagnetic cloaking, the thesis concluded after investigation that far more simple solutions that yield promising results exist. In terms of average sidelobe level in the antenna’s forward direction shell 2 of the PEC rhomb performed the best, with the second best realized gain behind shell 4 that successfully guided electromagnetic waves around the obstruction to the price of average sidelobe level. For solving the described problem scenario, the thesis recommends to slightly redesign shell 4 such that its outer dielectric rhomb point tips have a relatively lower permittivity as this likely will both effectively reduce the average sidelobe level and increase the realized gain for steering angles in the H-plane.
Keywords: Antenna obstruction cloaking; 9.5 GHz; X-band; electromagnetic cloak; anti-scattering; radiation absorbent; meta-material